Nylon moisturizing film and preparation method thereof

Through the composite technology of nylon, PP, PHA and other materials, combined with cooling masterbatch and nano-inorganic fillers, the moisturizing and mechanical properties of the nylon moisturizing film are improved, and the problems of moisture loss and insufficient mechanical properties during construction are solved, achieving more efficient Moisturizing effect and construction convenience.

CN119242025AActive Publication Date: 2025-01-03DONGGUAN ZHITENG PLASTIC PROD CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411502692.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-03
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The existing nylon moisturizing film has not been effectively solved during construction, and its mechanical performance is insufficient, which limits its wide application in construction projects.

Method used

Using nylon, PP, PHA, cooling masterbatch, maleic anhydride graft and nano-inorganic filler compounding technology, the flexibility, barrier properties and mechanical properties of the material are improved through blending modification and compatibility, ensuring moisturizing effect and construction convenience.

Benefits of technology

It significantly improves the moisturizing properties and mechanical properties of the nylon moisturizing film, reduces moisture loss and mechanical damage, improves construction efficiency and material durability, enhances the barrier ability to water vapor, and reduces manual maintenance workload.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005103012710000051
    Figure BDA0005103012710000051
  • Figure BDA0005103012710000061
    Figure BDA0005103012710000061
  • Figure BDA0005103012710000071
    Figure BDA0005103012710000071
Patent Text Reader

Abstract

The invention relates to the field of protective films, in particular to a nylon moisturizing film and a preparation method thereof. The composite material is prepared from the following raw materials in percentage by weight: 40 to 63 percent of nylon, 10 to 30 percent of PP (Polypropylene), 10 to 20 percent of PHA (Polyhydroxyalkanoate), 0.5 to 2 percent of cooling master batch, 3 to 8 percent of maleic anhydride graft, 0.3 to 1 percent of polyisobutylene succinimide, 1 to 8 percent of nano inorganic filler and the balance of processing aid. The nylon, the PP and the PHA are compounded, so that the performance can be synthesized, and the mechanical property and the barrier property to water vapor and the like are relatively good. In addition, through the interaction of the maleic anhydride graft, the polyisobutylene succinimide and the cooling master batch, the mixing uniformity of the nylon, the PP and the PHA is further improved, and the compatibility of the nano inorganic filler in a raw material system is promoted through the maleic anhydride graft and the polyisobutylene succinimide, so that the moisturizing property and the mechanical property are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of protective films, and more specifically, to a nylon moisturizing film and a preparation method thereof. Background Art

[0002] As an important part of the field of building materials technology, nylon moisturizing membrane is increasingly used in the construction industry. This membrane is mainly used to improve the moisturizing effect of poured concrete, thereby improving the thermal insulation effect, reducing the workload of manual maintenance, and effectively preventing concrete cracking. The use of nylon moisturizing membrane can significantly improve the construction quality and efficiency of concrete, reduce construction costs, and improve the safety and reliability of the construction process.

[0003] At present, in order to solve the problem of water loss during concrete construction, common solutions include the use of plastic film, moisturizers and fiber reinforcement materials. Plastic film is a common moisturizing method that can reduce water evaporation by covering the surface of poured concrete; moisturizers can be directly added to concrete to achieve a moisturizing effect by absorbing and retaining moisture; fiber reinforcement materials can improve the mechanical properties of concrete and indirectly reduce water loss.

[0004] However, the above technical solutions still have some defects. The plastic film can only simply cover the surface, cannot provide good barrier properties and mechanical strength, and is easily torn or ripped by the wind; the effect of the moisturizer is greatly affected by environmental factors, and the amount added is difficult to control; although the fiber-reinforced material can improve the mechanical properties of concrete, it has limited effect on moisture retention and cannot effectively prevent the rapid loss of water during construction. These defects limit the wide application of the above technical solutions in actual engineering. Summary of the invention

[0005] In order to improve the moisturizing effect of nylon moisturizing film on concrete and obtain better mechanical properties, the present application provides a nylon moisturizing film and a preparation method thereof.

[0006] In a first aspect, the present application provides a nylon moisturizing film, which is composed of the following raw materials in percentage by weight: Nylon: 40-63% PP: 10-30% PHA: 10-20% Cooling masterbatch 0.5-2% Maleic anhydride grafted compound: 3-8% Polyisobutylene succinimide 0.3-1% Nano inorganic filler: 1-8% The balance is processing aids.

[0007] By adopting the above technical solutions, the nylon moisturizing film has excellent flexibility and heat resistance while ensuring a good moisturizing effect, which can effectively prevent water loss and improve the convenience and durability of use during the construction process. Specifically, the nylon and PP blending modification improves the processing fluidity and impact strength of the material. The cooling masterbatch reduces the processing temperature and helps to improve the blending effect. The introduction of PHA enhances the barrier properties and biodegradability and improves the mechanical properties. Maleic anhydride grafts promote the compatibility between the components and ensure the uniform dispersion of the material. The selection of nano-inorganic fillers makes the nylon moisturizing film have a denser microstructure and enhances the ability to block gas and water molecules. Polyisobutylene succinimide and maleic anhydride grafts play a synergistic role, further improving the compatibility between nano-inorganic fillers and polymer matrix, and promoting the uniform dispersion of nano-inorganic fillers.

[0008] In summary, the present application utilizes nylon, PP, and PHA for compounding to combine their properties, so that their mechanical properties and barrier properties against water vapor are better. In addition, through the interaction between maleic anhydride grafts and cooling masterbatch, the mixing uniformity between nylon, PP, and PHA is further improved, and polyisobutylene succinimide and maleic anhydride grafts work synergistically to promote the compatibility and dispersibility of nano-inorganic fillers in the raw material system, and then combined with nylon, PP, and PHA, the moisturizing and mechanical properties of the nylon moisturizing film are further improved.

[0009] The nylon moisturizing film of the present application not only has a better ability to block water vapor transmission, but also has better mechanical properties, so that the nylon moisturizing film is applied to the forming process of building bridges, etc., plays a role in blocking water vapor, so that the building bridges, etc. can maintain better moisturizing properties, while reducing the possibility of damage during construction or use. The practicality of the nylon moisturizing film is improved.

[0010] Preferably, the maleic anhydride grafted material is one or more of maleic rosin, ethylene-butyl acrylate-glycidyl methacrylate terpolymer, and maleic anhydride-vinyl acetate copolymer.

[0011] By adopting the above technical scheme, the maleic anhydride grafted material is selected from one or more of maleic rosin, ethylene-butyl acrylate-glycidyl methacrylate terpolymer, and maleic anhydride-vinyl acetate copolymer, which not only improves the compatibility of PHA with nylon + PP, but also promotes the dispersion and compatibility of hexagonal silica, mica-like calcium carbonate, and wurtzite powder with the raw materials, further prevents the penetration of gas and water molecules, and makes the nylon moisturizing film have better mechanical properties, reducing the possibility of damage.

[0012] Preferably, the maleic anhydride grafted material is composed of maleic rosin, ethylene-butyl acrylate-glycidyl methacrylate terpolymer, and maleic anhydride-vinyl acetate copolymer in a weight ratio of 1:(1-2):(1-5).

[0013] By adopting the above technical scheme, the maleic anhydride grafted material is composed of maleic rosin, ethylene-butyl acrylate-glycidyl methacrylate terpolymer, and maleic anhydride-vinyl acetate copolymer in a specific proportion, which improves the compatibility of PHA with nylon + PP, and promotes the dispersion and compatibility of hexagonal silica, mica-like calcium carbonate, and wurtzite powder, thereby enhancing the mechanical properties of the nylon moisturizing film and reducing the possibility of damage.

[0014] Preferably, the particle size of the nano inorganic filler is 100-200 nm.

[0015] By adopting the above technical solution, the particle size of the nano inorganic filler is controlled within the range of 50-200nm, which effectively improves the density of the nylon moisturizing film and prevents the penetration of gas and water molecules, thereby enhancing the moisturizing effect and barrier performance.

[0016] Preferably, the nano inorganic filler is one or more of hexagonal silica, mica-like calcium carbonate, and wurtzite powder.

[0017] By adopting the above technical scheme, hexagonal silica, mica-like calcium carbonate, and wurtzite powder all have a hexagonal crystal structure and have a high filling density. As nano inorganic fillers, they can significantly improve the density and barrier properties of the nylon moisturizing film, effectively prevent the penetration of gas and water molecules, thereby better retaining the moisture inside the cement, improving the thermal insulation effect, and reducing the risk of concrete cracking.

[0018] Preferably, the nano inorganic filler is composed of hexagonal silica, mica-like calcium carbonate and wurtzite powder in a weight ratio of 3:(1-1.5):(0.3-0.8).

[0019] By adopting the above technical solution, hexagonal silica, mica-like calcium carbonate and wurtzite powder are combined in a specific weight ratio, which can give full play to their respective characteristics, effectively improve the density and barrier properties of the nylon moisturizing film, enhance the waterproof and air-proof effect of the material, and reduce the possibility of material damage.

[0020] Preferably, the number average molecular weight of the nylon is 15000-30000; the number average molecular weight of the PP is 40000-60000; and the number average molecular weight of the PHA is 30000-50000.

[0021] By adopting the above technical scheme, the number average molecular weight of nylon in the nylon moisturizing film is controlled within the range of 15000-30000, the number average molecular weight of PP is controlled within the range of 40000-60000, and the number average molecular weight of PHA is controlled within the range of 30000-50000, so that the material has more excellent mechanical properties and processing properties, further improving the overall performance and stability of the nylon moisturizing film.

[0022] Preferably, the processing aid is one or more of an antioxidant, an anti-UV agent, a lubricant, a plasticizer, and a colorant.

[0023] By adopting the above technical solutions, the nylon moisturizing film has comprehensive protective functions, which are specifically manifested in the characteristics of anti-oxidation, anti-ultraviolet, lubrication and increased plasticity. These characteristics work together, combined with nylon, PP, PHA, cooling masterbatch, maleic anhydride grafted products, and nano-inorganic fillers to improve the overall stability and service life of the nylon moisturizing film, ensuring that it can maintain excellent moisturizing effects and mechanical properties even in harsh environments, and reducing damage to the nylon moisturizing film caused by external factors. For example, when applied to moisturizing seaside bridge piers, it can reduce damage caused by wind, or excessive water loss in cement bridge piers during sun exposure, which affects construction efficiency.

[0024] Preferably, the antioxidant is one or more of antioxidant 1010, antioxidant 168, antioxidant 264, and antioxidant 1076; the anti-UV agent is UV-329 and / or UV-531; the lubricant is paraffin; and the plasticizer is a citrate plasticizer.

[0025] By adopting the above technical solutions, the nylon moisturizing film has better anti-oxidation, anti-ultraviolet, lubrication and plasticizing effects, which effectively improves the stability and service life of the nylon moisturizing film, reduces film damage and performance degradation caused by external environmental factors during construction, and further enhances the moisturizing effect and durability.

[0026] The present application provides a method for preparing a nylon moisturizing film, comprising the following steps: According to weight percentage, nylon, PP, cooling masterbatch and 1 / 2 maleic anhydride grafted product are weighed and mixed evenly, heated until melted, and stirred evenly to obtain a mixture A; Weigh PHA, polyisobutylene succinimide, nano inorganic filler, processing aid, and 1 / 2 maleic anhydride grafted product, mix them evenly, heat until melted, and stir evenly to obtain a mixture B; The mixture A is cooled, and is added to the mixture C while hot, and stirred evenly, and then extruded and calendered to obtain a nylon moisturizing film.

[0027] By adopting the above technical scheme, the preparation method ensures that nylon, PP, cooling masterbatch and part of maleic anhydride grafts are fully mixed and uniformly, and obtains mixture A in a molten state; PHA, nano inorganic filler, processing aid and remaining maleic anhydride grafts are also fully mixed and uniformly melted to obtain mixture B. By cooling mixture A and then mixing it with mixture B, it is ensured that the materials are fully mixed at a suitable temperature, and the nylon moisturizing film finally obtained by extrusion and calendering process has excellent moisturizing effect, high barrier performance, good flexibility and excellent biodegradability.

[0028] In summary, the present application includes at least one of the following beneficial technical effects: 1. By blending and modifying nylon and PP, and adding PHA, cooling masterbatch, polyisobutylene succinimide, maleic anhydride grafted products and nano inorganic fillers, the processing fluidity and mechanical properties of nylon moisturizing film, such as impact strength and toughness, can be significantly improved, thereby reducing damage caused by factors such as wind during construction; 2. By using hexagonal silica, mica-like calcium carbonate and wurtzite powder as nano inorganic fillers and using a specific ratio, the density of the material can be effectively improved, the barrier performance can be further improved, the penetration of gas and water molecules can be prevented, and the water loss during the concrete construction process can be effectively avoided; 3. The processing temperature is lowered by using cooling masterbatch, and the compatibility between raw materials is improved by maleic anhydride grafting, so that the nylon moisturizing film has better flexibility and thermal insulation effect, effectively improving the construction effect, while reducing the workload of manual maintenance and preventing concrete cracking. DETAILED DESCRIPTION

[0029] The present application is further described in detail below in conjunction with embodiments.

[0030] Introduction of some raw materials: The number average molecular weight of nylon is 100,000-200,000; The number average molecular weight of PP is 40,000-60,000; The number average molecular weight of PHA is 100,000-200,000; The preferred cooling masterbatch manufacturer model is Huizhou Yupu Chemical Co., Ltd. model YP027; The preferred model of Malay rosin manufacturer is MR-115# from Xiamen Weier Chemical Co., Ltd.; The brand model of ethylene-butyl acrylate-glycidyl methacrylate terpolymer is American DuPont PTW-1 toughening agent; The number average molecular weight of maleic anhydride-vinyl acetate copolymer is 850-1000; The number average molecular weight of polyisobutylene succinimide is 10000-2000. Example

[0031] Example 1 A method for preparing a nylon moisturizing film comprises the following steps: According to the weight percentage, 40% nylon, 30% PP, 2% cooling masterbatch and 4% maleic anhydride grafted material were weighed and mixed evenly, heated to 230° C. to make them all melted, and stirred at a speed of 30 r / min for 10 minutes to make them fully stirred to obtain a mixture A; 10% PHA, 1% polyisobutylene succinimide, 8% nano inorganic filler, 2% processing aid, and 4% maleic anhydride graft were weighed and put into a heating and stirring device to mix evenly, and then heated to 180° C. to melt the PHA, maleic anhydride graft, and processing aid, and stirred at a speed of 30 r / min for 10 minutes to fully stir and obtain a mixture B; The mixture A was cooled to 185°C, added to the mixture C while hot, and stirred for 10 minutes to fully mix the mixture to obtain the mixture C. The mixture was then transferred to an extruder for extrusion, and then calendered through a calendering device to obtain a nylon moisturizing film with a thickness of 125 microns.

[0032] Among them, the industrial auxiliary agent is antioxidant, anti-UV agent, and plasticizer in a weight ratio of 1:1:2; the antioxidant is antioxidant 1010; the anti-UV agent is UV-329; the plasticizer is tributyl citrate. The number average molecular weight of nylon is 30000g / mol; the number average molecular weight of PP is 40000g / mol; the number average molecular weight of PHA is 30000g / mol.

[0033] Example 2-3 The difference between Example 2-3 and Example 1 is that the amount of the nylon moisturizing film raw material is different, as shown in Table 1: Table 1 Raw material usage of Examples 1-3 % Example 4 The difference between Example 4 and Example 2 is that the maleic anhydride grafted material is an ethylene-butyl acrylate-glycidyl methacrylate terpolymer.

[0034] Example 5 The difference between Example 5 and Example 2 is that the maleic anhydride grafted material is maleic anhydride-vinyl acetate copolymer.

[0035] Example 6 The difference between Example 6 and Example 2 is that the maleic anhydride grafted material is composed of maleic rosin and ethylene-butyl acrylate-glycidyl methacrylate terpolymer in a weight ratio of 1:1.

[0036] Example 7 The difference between Example 7 and Example 2 is that the maleic anhydride grafted material is composed of maleic rosin, ethylene-butyl acrylate-glycidyl methacrylate terpolymer, and maleic anhydride-vinyl acetate copolymer in a weight ratio of 1:1:1.

[0037] Example 8 The difference between Example 8 and Example 2 is that the maleic anhydride grafted material is composed of maleic rosin, ethylene-butyl acrylate-glycidyl methacrylate terpolymer, and maleic anhydride-vinyl acetate copolymer in a weight ratio of 1:2:3.

[0038] Example 9 The difference between Example 9 and Example 2 is that the maleic anhydride grafted material is composed of maleic rosin, ethylene-butyl acrylate-glycidyl methacrylate terpolymer, and maleic anhydride-vinyl acetate copolymer in a weight ratio of 1:2:5.

[0039] Example 10 The difference between Example 10 and Example 8 is that the nano inorganic filler is mica-like calcium carbonate.

[0040] Embodiment 11 The difference between Example 11 and Example 8 is that the nano inorganic filler is wurtzite powder.

[0041] Example 12 The difference between Example 12 and Example 8 is that the nano inorganic filler is composed of mica-like calcium carbonate and wurtzite powder in a weight ratio of 1:2 composition.

[0042] Embodiment 13 The difference between Example 13 and Example 8 is that the nano inorganic filler is composed of hexagonal silica, mica-like calcium carbonate, and wurtzite powder in a weight ratio of 3:1:0.3.

[0043] Embodiment 14 The difference between Example 14 and Example 8 is that the nano inorganic filler is composed of hexagonal silica, mica-like calcium carbonate, and wurtzite powder in a weight ratio of 3:1.5:0.5.

[0044] Embodiment 15 The difference between Example 15 and Example 8 is that the nano inorganic filler is composed of hexagonal silica, mica-like calcium carbonate, and wurtzite powder in a weight ratio of 3:1.1:0.8.

[0045] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that PHA is replaced by nylon in equal amounts.

[0046] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that PP is replaced by nylon in equal amounts.

[0047] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that an equal amount of nylon is replaced by PP.

[0048] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that an equal amount of polyisobutylene succinimide is replaced by nylon.

[0049] Performance testing Detection method / test method Water vapor permeability test: Test the water vapor permeability in accordance with GB1037-88 Test method for water vapor permeability of plastic film and sheet.

[0050] Mechanical properties: The mixture C obtained in Examples 1-15 and Comparative Examples 1-4 was transferred to an injection molding machine and injection molded at 190° C. to form a test specimen, and the elongation at break and tensile strength were tested with reference to ASTM D638.

[0051] The above experiments were tested 5 times and the average value was taken; Table 2 Experimental data of Examples 1-15 and Comparative Examples 1-4 Combining Example 1 and Comparative Examples 1-4 and Table 2, it can be seen that the water vapor permeability of Comparative Examples 1-3 is significantly increased, and the tensile strength and elongation at break of Comparative Examples 1-3 are lower than those of Example 1, indicating that the use of the PHA, PP, nylon, combined nylon, PP, PHA, cooling masterbatch, maleic anhydride graft, nano inorganic filler, etc. of the present application for compounding has better water vapor barrier properties and mechanical properties, reduces the phenomenon of damage to the nylon protective film, and improves its moisture retention and practicality.

[0052] Comparing Example 2 with Example 8 and combining with Table 2, it can be seen that the water vapor transmission rate is reduced to 13g / m 2 ·24h (Example 2 is 23g / m 2 ·24h), and the tensile strength and elongation at break of Example 8 are both improved, indicating that the maleic rosin, ethylene-butyl acrylate-glycidyl methacrylate terpolymer, and maleic anhydride-vinyl acetate copolymer used in Examples 7-9 are compounded to play a synergistic role and further improve the comprehensive properties of the nylon film.

[0053] Comparing Example 8 and Example 14 and combining with Table 2, it can be seen that the water vapor transmission rate is reduced to 5g / m 2 ·24h (Example 8 is 13g / m 2 ·24h), and the tensile strength of Example 8 reaches 58Mpa (Example 8 is 50Mpa), and the elongation at break is increased by 223% (Example 8 is 185%), which shows that when hexagonal silica, mica-like calcium carbonate, and wurtzite powder are compounded, a synergistic effect is played, and the mechanical properties and water vapor barrier properties of the nylon moisturizing film are further improved, thereby having a better moisturizing effect on concrete and improving its practicability.

[0054] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A nylon moisturizing film, characterized in that: The following raw materials are used in proportion by weight: composition: Nylon: 40-63% PP: 10-30% PHA: 10-20% Cooling masterbatch 0.5-2% Maleic anhydride grafted compound: 3-8% Polyisobutylene succinimide: 0.3-1% Nano inorganic filler: 1-8% The balance is processing aids.

2. A nylon moisturizing film according to claim 1, characterized in that: The maleic anhydride grafted material is one or more of maleic rosin, ethylene-butyl acrylate-glycidyl methacrylate terpolymer, and maleic anhydride-vinyl acetate copolymer.

3. A nylon moisturizing film according to claim 2, characterized in that: The maleic anhydride grafted material is composed of maleic rosin, ethylene-butyl acrylate-glycidyl methacrylate terpolymer, and maleic anhydride-vinyl acetate copolymer in a weight ratio of 1: (1-2): (1-5).

4. The nylon moisturizing film according to claim 1, characterized in that: The particle size of the nano inorganic filler is 100-200nm.

5. The nylon moisturizing film according to claim 1, characterized in that: The nano inorganic filler is one or more of hexagonal silicon dioxide, mica-like calcium carbonate and wurtzite powder.

6. A nylon moisturizing film according to claim 5, characterized in that: The nano inorganic filler is composed of hexagonal silicon dioxide, mica-like calcium carbonate and wurtzite powder in a weight ratio of 3: (1-1.5): (0.3-0.8).

7. The nylon moisturizing film according to claim 1, characterized in that: The number average molecular weight of the nylon is 15000-30000; the number average molecular weight of the PP is 40000-60000; the number average molecular weight of the PHA is 30000-50000.

8. The nylon moisturizing film according to claim 1, characterized in that: The processing aid is one or more of an antioxidant, an anti-UV agent, a lubricant, a plasticizer, and a colorant.

9. The nylon moisturizing film according to claim 1, characterized in that: The antioxidant is one or more of antioxidant 1010, antioxidant 168, antioxidant 264, and antioxidant 1076; the anti-UV agent is UV-329 and / or UV-531; the lubricant is paraffin; and the plasticizer is a citrate plasticizer.

10. A method for preparing a nylon moisturizing film according to any one of claims 1 to 9, characterized in that: The following steps are involved: According to weight percentage, nylon, PP, cooling masterbatch and 1 / 2 maleic anhydride grafted product are weighed and mixed evenly, heated until melted, and stirred evenly to obtain a mixture A; Weigh PHA, polyisobutylene succinimide, nano inorganic filler, processing aid, and 1 / 2 maleic anhydride grafted product, mix them evenly, heat until melted, and stir evenly to obtain a mixture B; The mixture A is cooled, and is added to the mixture C while it is hot, and stirred evenly, and then extruded and calendered to obtain a nylon moisturizing film.

Citation Information

Patent Citations

  • Nylon composite material containing bio-based high molecules and preparation method thereof

    CN102516762A

  • Low-water absorption polyamide 66 / polypropylene alloy material

    CN102675871A

  • Polypropylene cooling masterbatch and preparation method thereof

    CN102863694A

  • Modified PA compound material and production method thereof

    CN109971164A

  • Nylon 6 / polypropylene composite material as well as preparation method and application thereof

    CN114806153A